PENGARUH CELEBRITY ENDORSER, CITRA MEREK, DAN IKLAN TELEVISI TERHADAP KEPUTUSAN PEMBELIAN PRODUK LUWAK WHITE KOFFIE DI KECAMATAN PUCAKWANGI KABUPATEN PATI - Sri Mulyani Endrawati, 15.05.51.0215; Soliha, Euis (Students' Journal of Economic and Management, 2019)
This study aims to examine the influence of celebrity endorser, brand image, television advertising on purchasing decision. The population in this research were consumers of Luwak White Koffie products in Pucakwangi District, Pati Regency with a total sample of 100 respondents using purposive sampling method. This research proposes three hypotheses, they are celebrity endorser has a positive effect on purchasing decisions, brand image has a positive effect on purchasing decisions, and television advertising has a positive effect on purchase decisions. This research tested using instrumen test which include validity and reliability tests, and multiple linear regression using the SPSS application. Based on the statistic test, it can be concluded that celebrity endorser has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, television advertising has a positive and significant effect on purchasing decisions.